A novel method based on self-sensing motor drive system for misalignment detection. (1st February 2019) - Yao, Yuan; Li, Yesong; Yin, Quan
Highlights: The research aims at problem caused by additional sensor during fault diagnosis. The self-sensing property of motor drive is revealed to detect mechanical faults. The virtual phase torque diagram method is proposed to provide multivariable sensing. We classify different misalignments in experiments, using the VPT diagram. Abstract: In the diagnosis of electromechanical system, traditional vibration analysis methods are affected by the positioning of additional sensors. To overcome this problem, we propose a virtual phase torque (VPT) diagram method based on self-sensing motor drive system. Firstly, the q-axis current is obtained from field oriented control (FOC) process of permanent magnet synchronous motor (PMSM) drive system and used for load torque sensing. Then, fault components extracted from q-axis current and the phase angle from motor encoder are combined together to form the VPT diagram to detect the offset angle of misalignment. Therefore, misalignments in different directions can be classified. Simulations and experiments using a ball screw platform are implemented to validate the proposed method.